Sociodemographic characteristics in primigravida puerperal women the first fifteen days post partum. Sergio Bernales Hospital Lima - Moncada-Luna, Rodolfo A. (2019)
The problem in this work was what are the frequent support needs in breastfeeding according to sociodemographic characteristics on primigravida puerperal women during the first 15 days from Sergio Bernales Hospital - Lima? the objective was to determine the needs of frequent support in breastfeeding according to sociodemographic characteristics and, as a hypothesis, the most frequent support needs in breastfeeding are differentiated according to the sociodemographic characteristics in primigravida puerperal women during the first fifteen days from Sergio Bernales Hospital - Lima. The study was descriptive - comparative with 95 primigravida puerperal women. We used an interview guide for data collection. In the inferential analysis of the results, it was used the Chi square test, obtaining as a result that 55.8% had emotional support needs, 69.5% educational support and 93.7% practical support, concluding that the most frequent support needs in breastfeeding are differentiated according to the sociodemographic characteristics of primigravida puerperal women from Sergio Bernales Hospital Lima.